Pengaruh NPL dan LDR Terhadap Kinerja Keuangan dengan NIM Sebagai Variabel Intervening - Laily Yuli Astuti; Achmad Badjuri (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Factors that affect financial performance can come from various profitability performance indicated by several indicators. Measuring the level of profitability is very important, this aims to guarantee whether the profits targeted by the company in several periods have been achieved. This study aims to examine NPL and LDR on financial performance proxied by ROA with NIM as the intervening variable. The population used in this study were banks listed on the IDX for the 2020-2022 period, with a total population of 47 banks. Sampling was carried out using purposive sampling method, so that 40 banks are obtained. Data analysis techniques in this study were carried out using multiple linier regression analysis methods. The results showed that NPL had a negative effect on NIM. LDR has no effect on NIM. NPL has a negative effect on ROA. LDR has no effect on ROA. NIM has a positive effect on ROA. NIM cannot mediate NPL and LDR against ROA. Keyword : NPL, LDR, NIM, ROA